2*(x+7) = 5x-1
2x + 14 = 5x-1
14+1 = 5x-2x
15 = 3x
x = 5
2*(x+7)=5x-1 - раскрываем скобки
2х + 14 = 5х - 1 - переносим, не забываем про противоположные знаки
2х - 5х = -1 - 14 - считаем
-3х = - 15
х = (-15) : (-3)
х = 5
ПРОВЕРКА:
2 х (5 + 7) = 5 х 5 - 1
10 + 14 = 25 - 1
24 = 24
2*(x+7) = 5x-1
2x + 14 = 5x-1
14+1 = 5x-2x
15 = 3x
x = 5
2*(x+7)=5x-1 - раскрываем скобки
2х + 14 = 5х - 1 - переносим, не забываем про противоположные знаки
2х - 5х = -1 - 14 - считаем
-3х = - 15
х = (-15) : (-3)
х = 5
ПРОВЕРКА:
2 х (5 + 7) = 5 х 5 - 1
10 + 14 = 25 - 1
24 = 24